Lorcaserin Alters Serotonin and Noradrenaline Tissue Content and Their Interaction With Dopamine in the Rat Brain - Di Giovanni, Giuseppe; Bharatiya, Rahul; Puginier, Emilie; Ramos, Marta; De Deurwaerdère, Salomé; Chagraoui, Abdeslam; De Deurwaerdère, Philippe (Frontiers in Pharmacology, 2020)
Lorcaserin is a preferential serotonin2C receptor (5-HT2CR) agonist effective to treat obesity that has also recently been proposed to treat addiction and epilepsy. Central dopamine (DA) mechanisms are likely involved in the lorcaserin mechanism of action, but other monoamines 5-HT and noradrenaline (NA) contents or their interaction with DA might account for its effects. Here we showed that lorcaserin at 3, but not 0.3 mg/kg enhanced 5-HT content in the insular cortex, the core of the nucleus accumbens, and ventral hypothalamus. Without affecting the metabolite 5-hydroxy-indole acetic acid, lorcaserin reduced the indirect index of 5-HT turnover in the hippocampus, substantia nigra, and habenula. Lorcaserin at 3 mg/kg increased NA content in the orbitofrontal cortex, the central amygdala (also at 0.3 mg/kg), the ventral hypothalamus, and the shell of the nucleus accumbens. A correlative analysis of the tissue contents between pairs of brain regions revealed that 0.3 mg/kg lorcaserin enhanced the number of correlations for 5-HT, its metabolism, and NA to a lower extent. The correlation profiles were very different between saline, 0.3 and 3 mg/kg lorcaserin. Lorcaserin enhanced the correlations established between NA or 5-HT at 0.3 and 3 mg/kg and reduced the number of correlations established between the index of the turnover for DA and 5-HT. These results show that lorcaserin modulates the biochemistry of NA and 5-HT systems in a subset of brain regions. Qualitatively, they reveal, oppositely to the DA changes, that lorcaserin at 0.3, but not 3 mg/kg, enhanced the number of correlations of 5-HT content between brain regions.